Diatoms from Southwest Greenland. - Foged, Niels (Meddelelser om Grønland, 1973)
In material collected in 195? and 19?0 in localities situated between 59° 44’ N and 61 °22’N in SW Greenland a total of 465 oligohalobous diatoms and 260 mesohalobous and polyhalobous diatoms is shown, 4 nov. var. and 4 nov. fo. included. A great number of the species and their varieties are not previously shown in Greenland. Chemical analyses of 31 water samples are given. 439 photos of 284 different diatoms 193 oligohalobous and 91 mesohalobous or polyhalobous forms) are reproduced in 29 plates.